1996
DOI: 10.1007/bf01979446
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric spectroscopy and calorimetry in the glass transition region of semi-crystalline poly(ethylene terephthalate)

Abstract: Confinement of the glass-forming regions in the nanometer range influences the (x-relaxation which is associated with the glass transition. These effects were investigated for semicrystalline poly(ethylene terephthalate) by dielectric spectroscopy and differential scanning calorimetry. The. results are discussed within the concept of cooperative length, i.e. the characteristic length of the cooperative process of glass transition. Both experiments showed a dependence of the glass transition on the mean thickne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
87
0
6

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(101 citation statements)
references
References 30 publications
8
87
0
6
Order By: Relevance
“…Moreover, investigation of the relaxation intensity in most semicrystalline polymers shows that not all the non-crystalline fraction participates in the glass transition. 11 Therefore, a rigid amorphous and mobile amorphous fraction has been postulated. The mobile amorphous fraction contributes to the glass transition.…”
Section: Results and Discussion Effect Of Orientationmentioning
confidence: 99%
“…Moreover, investigation of the relaxation intensity in most semicrystalline polymers shows that not all the non-crystalline fraction participates in the glass transition. 11 Therefore, a rigid amorphous and mobile amorphous fraction has been postulated. The mobile amorphous fraction contributes to the glass transition.…”
Section: Results and Discussion Effect Of Orientationmentioning
confidence: 99%
“…(1) we can calculate the mobile amorphous fraction related to the local movements from the relaxation strength of the ~-relaxation. We compare the results with that of the dynamic glass transition (main-, a-relaxation) [6].…”
Section: John Wiley and Sons Limited Chichestermentioning
confidence: 88%
“…In an earlier study on isothermal crystallization of poly(aryl ether ketone ketone), Ezquerra et al 19 showed a very strong correlation between the strength of the dielectric relaxation, ⌬⑀ ϭ ⑀ 0 Ј Ϫ ⑀ ϱ Ј (where ⑀ ϱ Ј is the unrelaxed, highfrequency permittivity) and the crystallinity, as calculated from X-ray images. This and other studies 9,13,16,31,32 have shown that the extrapolation of crystallinity to ⌬⑀ ϭ 0 yields in some polymers a predicted crystallinity somewhat lower than 100%. However, we felt justified in using dielectric measurements to determine relative crystallization kinetics for our isothermally grown PDS films because this material typically crystallizes under good conditions to only about 40%.…”
Section: Crystallization Kinetics Based On Relaxed Permittivity Measumentioning
confidence: 89%